Lot sizing and furnace scheduling in small foundries - Araujo, Silvio A. de; Arenales, Marcos N.; Clark, Alistair R. (Elsevier, 2008)
A lot sizing and scheduling problem prevalent in small market-driven foundries is studied. There are two related decision levels: (1) the furnace scheduling of metal alloy production, and (2) moulding machine planning which specifies the type and size of production lots. A mixed integer programming (MIP) formulation of the problem is proposed, but is impractical to solve in reasonable computing time for non-small instances. As a result, a faster relax-and-fix (RF) approach is developed that can also be used on a rolling horizon basis where only immediate-term schedules are implemented. As well as a MIP method to solve the basic RF approach, three variants of a local search method are also developed and tested using instances based on the literature. Finally, foundry-based tests with a real-order book resulted in a very substantial reduction of delivery delays and finished inventory, better use of capacity, and much faster schedule definition compared to the foundry's own practice. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Lot sizing and scheduling; Meta-heuristics; Mixed integer programming; Heuristic algorithms; Integer programming; Metadata; Problem solving; Tabu search; Metaheuristics; Scheduling